THE THE EFFECTIVENESS OF THE CREATIVE PROBLEM SOLVING LEARNING MODEL IN TERMS OF STUDENTS' MATHEMATICAL REASONING AND COMMUNICATION SKILLS - Antonius KAP Simbolon (Nusantara Hasana Berdikari, 2022)
The purpose of this study is to describe the differences in the effectiveness of creative problem solving learning models and conventional learning models in terms of reasoning, communication, and self-esteem abilities. This research is a quasi-experimental research with a non-equivalent comparison group design. The research subjects were students at SMP Negeri 2 Tanjung Morawa. The sample consisted of 50 students from two class VII, each of which followed the conventional learning model and creative problem solving learning model. The research instrument consisted of a test of students' reasoning abilities and a test of students' mathematical communication skills. The analysis technique uses descriptive analysis and Hotteling's Trace. The results of the study at the 5% significance level showed that: (1) the creative problem solving learning model was effective in terms of students' mathematical reasoning and communication abilities; (2) the conventional learning model is effective in terms of students' mathematical reasoning and communication abilities; and (3) there is a difference in effectiveness between creative problem solving and conventional learning models in terms of students' mathematical reasoning and communication abilities.